2021
DOI: 10.1038/s41467-021-22636-9
|View full text |Cite
|
Sign up to set email alerts
|

Histone dynamics mediate DNA unwrapping and sliding in nucleosomes

Abstract: Nucleosomes are elementary building blocks of chromatin in eukaryotes. They tightly wrap ∼147 DNA base pairs around an octamer of histone proteins. How nucleosome structural dynamics affect genome functioning is not completely clear. Here we report all-atom molecular dynamics simulations of nucleosome core particles at a timescale of 15 microseconds. At this timescale, functional modes of nucleosome dynamics such as spontaneous nucleosomal DNA breathing, unwrapping, twisting, and sliding were observed. We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(101 citation statements)
references
References 80 publications
6
95
0
Order By: Relevance
“…Histone tails have a high degree of conformational flexibility and might protrude into the solvent and remain perpetually accessible for binding by chromatin factors 1 , 8 10 . However, there is growing evidence that histone tails can extensively interact with the nucleosomal and linker DNA 11 – 19 , which raises the possibility that tails may modulate the nucleosomal and linker DNA accessibility and regulate the nucleosome recognition by binding partners. It has been shown that despite the lower net negative charge of the nucleosome compared to the free DNA, nucleosomes are characterized by an enhanced negative charge density (so-called electrostatic focusing) even with the intact positively charged histone tails 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Histone tails have a high degree of conformational flexibility and might protrude into the solvent and remain perpetually accessible for binding by chromatin factors 1 , 8 10 . However, there is growing evidence that histone tails can extensively interact with the nucleosomal and linker DNA 11 – 19 , which raises the possibility that tails may modulate the nucleosomal and linker DNA accessibility and regulate the nucleosome recognition by binding partners. It has been shown that despite the lower net negative charge of the nucleosome compared to the free DNA, nucleosomes are characterized by an enhanced negative charge density (so-called electrostatic focusing) even with the intact positively charged histone tails 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Because histone proteins are tightly wrapped by double-stranded DNA in the nucleus to compress DNA into chromatin, interaction between histones and DNA is crucial for gene activity [ 57 ]. In further detail, since DNA binds to an octamer structure of the histone complex, (H3, H4) 2 (H2A, H2B) 2 , histones may release or capture DNA to turn-on or turn-off gene expression, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, there is a lack of studies investigating the function of this modification. The arginine residue 49 is thought to interact with the DNA and postulated to regulate gene expression by affecting H3K56ac (transcriptional activation) [ 68 70 ]. To a lesser extent, H3R42me2, linked to transcriptional activation, was increased under all treatments [ 71 ].…”
Section: Discussionmentioning
confidence: 99%